ITIKAD BAIK PADA PENDAFTARAN HAK ATAS TANAH DALAM SISTEM HUKUM PERTANAHAN - Setyo Putri, Ayu Bimo (Jurnal Cakrawala Hukum, 2017)
In 1961 the government enacted Government Regulation No. 10 of 1961 on Land Registration, but this regulation can no longer fully achieve maximum results in national development, so it is deemed necessary to make improvements. The purpose of this study is to know and analyze the meaning and benchmarks of good faith in Article 24 Paragraph (2) of Government Regulation No. 24 of 1997 which regulates the procedure of registration of land rights derived from the old right, if evidence is lacking or not at all. This study uses a type of normative juridical research using the approach of legislation and conceptual approach. The meaning of good faith from the experts is not contrary to the existing rules, proper, honest, and does not intend to enrich themselves by harming others. A good measure of faith in the registration of physically controlled land rights uses objective benchmarks in an objective way, if all requirements are met, then it can be said to be in good faith. The procedure provided by this Regulation has provided justice and legal certainty, as the procedure is clear, and if the applicant is proven to do the forbidden, then it may be criminally and civil liable. Â